Silicone Oil Induced Glaucoma - Madhu Bhoot; Ankita Agarwal; Suneeta Dubey; Julie Pegu; Monica Gandhi (Delhi Journal of Ophthalmology)
Silicone oil (SO) is a vitreous substitute which is widely used to provide long term intraocular tamponade in retinal surgery. Transient or permanent rise in intraocular pressure is a common complication of silicone oil injection following pars plana vitrectomy. The underlying mechanisms include pupillary block, infiltration of the trabecular meshwork by silicone bubbles, trabeculitis, synechial angle closure, rubeosis iridis and migration of emulsified and non emulsified silicone oil into the anterior chamber. Most of the cases can be managed medically, however, surgical intervention in the form of silicone oil removal, trabeculectomy with or without Mitomycin C, glaucoma drainage implants and cyclodestructive procedures may be required in cases unresponsive to conservative management.